A questão do politicamente correto em temáticas relativas à homossexualidade e seus reflexos na representação da informação - Cabrera, Miriam Regiane Dutra [UNESP] (2012)
Whereas the ethical aspects involved in the thematic representation to influence the professional librarian and document that the language changes with the inclusion of new perceptions of reality, it is important to analyze the peculiarities of the movement of political correctness as a subsidy to the study of its impacts the representation of information, specifically the themes related to homosexuality. Thus, aiming to contribute to sedimentation in the area of theoretical research in Ethics in the representation of information with regard to issues related to homosexuality, aimed to: a) analyze the peculiarities of the movement of political correctness as a subsidy to the study of their impacts on the representation of information, b) analyze the issues relating to homosexuality as an aid to study their impact on the representation of information, c) identify the international literature of information science that has been dedicated to the confluence between the themes of homosexuality, political correctness and representation information; d) to signal prospects of professional action regarding the representation of information on subjects relating to homosexuality in the context of political correctness. To do so, broke a theoretical approach to the ethical representation of information, from which have been specifically studied the issues of political correctness and the issue of homosexuality under the watchful historical, social and informational. Next, we sought to identify, ma international literature of Information Science (LISA basis) of the last decade, have been treated as issues of representation of information on topics related to the politically correct view of homosexuality, from the political search... (Complete abstract click electronic access below)